Traditional Dance Movement as an Inspiration for Students of SMP N 1 Kalasan Sleman Yogyakarta: Challenges and Innovation in Performance - Enis Niken Herawati, Enis Niken (Catharsis, 2025)
This study discusses the use of traditional dance movements as a source of inspiration and educational media for students at SMP Negeri 1 Kalasan, Sleman, Yogyakarta. Traditional dance movements were chosen because they have strong cultural values and play an important role in shaping character and enriching artistic insights for the younger generation. The main purpose of this study is to analyze the challenges faced in the process of teaching and implementing traditional dance in schools, as well as to identify various innovations in the implementation of dance performances that can increase students' interest and participation. The research method used is a qualitative approach with data collection techniques in the form of observation, interviews, and documentation.The results of the study show that the main challenge faced is the lack of support resources and students' interest in traditional dance, but innovations in performance concepts such as the use of visual technology, incorporation with modern music, and collaboration between students are able to create an interesting and relevant experience. This study concludes that traditional dance movements can not only be used as a medium for cultural preservation, but also as a creative means to develop students' potential in dance.